Shortcuts to adiabaticity in a fast controlled-phase gate in superconducting quantum circuits - Li, Jia-Xin; Cárdenas-López, F. A.; Chen, Xi (Frontiers in Quantum Science and Technology, 2023)
Based on renewed interest in the shortcut-to-adiabaticity techniques in quantum control, we propose a reverse-engineering approach to modulate the longitudinal coupling between a pair of two-level systems with a quantized single-mode resonator. This allows us to suppress the unwanted transitions in the time-evolution operator such that the system dynamics resemble a controlled-phase gate acting in the qubit subspace at the nanosecond scale. The reduced gating time mitigates the detrimental effect produced by the loss mechanisms in all aspects. Moreover, we present a possible experimental implementation based on superconducting quantum circuits. Our work further demonstrates the versatility of the reverse-engineering method to enhance quantum protocols based on circuit quantum electrodynamic architecture.